Determinants Identification of Poverty and Human Capital of Fisherman Household - Aning Kesuma Putri (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
This research was conducted to see the determinants of poverty and human capital in fishermen households in Bangka and Pangkalpinang (Bangka Belitung Province, Indonesia). The research was conducted in Fisherman I and Temberan Village, Air Itam and Sinarbulan. The samples were 118 fishermen, 59 households in Fisherman I and Temberan Village, Air Itam and Sinarbulan by distributing questionnaires. The research method used qualitative and quantitative with SPSS tool. The results show that poverty and human capital are defined as 15% in Fisherman Environment I and 1.4%, meaning that other variables such as human resources, fishermen lending, fishermen institutions and other variables have an enormous effect on poverty and human capital. Further research should be done to look at the pattern of households of young fishermen and households of elderly fishermen.